A Semantic Analysis for Internet of Things - Yinghui Huang; Guanyu Li (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
This paper focuses on the concept itself of Internet of Things, which are related to the literal meaning, the internal property and the external relation. Analyzing the semantic meaning of the word internet of things can help to understand the properties of Internet of Things. Comparing the similarities and differences of the entity Internet of Things and other Internet applications can help to classify the entity. The actual semantics of Internet of Things is Internet of product information, a new type of Internet application. The properties of Internet of Things include the dominance and the attributes. The former means the interconnection of product information in different parts of the world based on Internet, while the latter further explains the three restrictive characters of the product information, namely the electronic tag form, the standardizing restraint, and the ontology supporting. The product information is written in an electronic tag by used the standard words whose semantic meanings are explained in one or more of ontology, so it can be read and understood by a computer. Internet of Things can be seen as a specific application form of Semantic Web.